Recent developments in fault location methods for distribution networks - Awalin, L.J.; Mokhlis, Hazlie; Bakar, A.H.A. (Przeglad Elektrotechniczny, 2012)
Reliability and quality of electrical power supply are always affected by the occurrence of faults in the distribution networks. However, the reliability and quality indices of power supply could be improved by locating the fault in minimum time. This task could only be achieved by using automated fault location methods. Various fault location methods have been developed with the main objective to expedite the locating time of the fault and thereby reducing the interruption duration. Considering the important needs of automated fault location methods, the aim of this paper is to review the most recent fault location methods in the literature specifically for distribution networks. The reported papers are from journals and proceedings from year 2005 to 2011. The working principle, strength and limitation of each method are discussed in this paper to highlight possible research opportunities in this area.